Immersive Technologies-Driven Building Information Modeling (BIM) in the Context of Metaverse - Zhen Liu; Shiqi Gong; Zhiya Tan; Peter Demian (Buildings, 2023)
At present, considering the novelty of Immersive Technologies (ImTs) associated with Digital Twin (DT), Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR) in the context of the metaverse and its rapid and ongoing development in Building Information Modeling (BIM), knowledge of specific possibilities and methods for integrating ImTs into building process workflows remains fragmented and scarce. Therefore, this paper aims to explore the research progress and trends of immersive technology-driven BIM applications, providing a helpful reference for understanding the current knowledge system and stimulating future research. To the best of the authors’ knowledge, this is the first attempt to use macro-quantitative bibliometric analysis and micro-qualitative analysis methods to explore the research topic of ImTs-driven BIM. This study obtains 758 related studies in the past decade, year 2013 to 2022, through a series of keywords from the Web of Science Core Collection database and uses VOSviewer software to conduct keywords co-occurrence analysis and overlay visualisation to visualise the relationship between ImTs and BIM, which contains six clusters, namely VR, Internet of Things (IoT), DT, 3D model, design, and AR. The macro-quantitative analysis on ImTs-driven BIM applications throughout all the stages of the building lifecycle reveals the themes, content, and characteristics of the applications across the stages, which tend to be integrated with emerging advanced technology and tools, such as Artificial Intelligence (AI), blockchain, and deep learning.